Genetic and environmental contributions to stability and change in social inhibition across the adolescent and adult life span - Li-Gao, Ruifang; Boomsma, Dorret I; Dolan, Conor V; De Geus, Eco J C; Denollet, Johan; Kupper, Nina (Developmental psychology, 2022)
Feeling inhibited and socially not at ease is reflected in the trait social inhibition (SI). SI is associated with psychopathology that arises in young adulthood, such as anxiety. We aim for a better insight into the genetic and environmental contributions to SI across the life span, and as such examine their contributions to SI stability and change across adolescent and adult life span. We analyzed cohort-sequential longitudinal data from the Netherlands Twin Register (NTR), spanning a period of 25 years (Men (N, %): 17855, 37.4%; Age (Median, IQR): 19 years, 16-26 years; 7474 complete MZ twins and 8799 complete DZ twins). The data were organized into 7 age groups: < 14 (preadolescence), 15-16 (early adolescence), 17-18 (mid adolescence), 19-20 (late adolescence), 21-30 (young adulthood), 31-40 (adulthood), 41 + (middle-age-older adulthood). SI was assessed with the ASEBA-based proxy questionnaire. Phenotypic stability was established across the entire age range. Next, a longitudinal genetic simplex model was fitted to estimate the genetic and environmental contributions to the observed phenotypic stability. Results showed SI correlated well across follow-up of a single decade (.44 ≤ r ≤ .59) and moderately across the 25 years (.23 - .32) from adolescence to middle-age and older. Broad-sense heritability (h²) was between 40 and 48% across the 7 age groups. Additive and nonadditive genetic effects together explained most of the stability of SI across the life span (about 60-90% of the phenotypic correlation between ages), whereas environmental effects played a lesser role (about 10-40%). Concluding, SI, known to increase the risk of internalizing psychopathology, is phenotypically stable across the life span, which is largely attributable to genetic contributions to individual differences in SI. (PsycInfo Database Record (c) 2022 APA, all rights reserved).